Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1262/jrd.20062
|View full text |Cite
|
Sign up to set email alerts
|

Fertility after Different Artificial Insemination Methods Using a Synthetic Semen Extender in Sheep

Abstract: Abstract. The present study aimed to investigate the fertility of ewes artificially inseminated with three different methods using a synthetic semen extender, AndroMed. The three methods of artificial insemination (AI) were cervical AI with fresh-diluted or frozen-diluted semen at observed estrus, and an intrauterine AI with frozen-thawed semen. A total of 80 ewes were treated with a controlled internal drug release (CIDR) containing 0.3 g progesterone per device for 12 days. In Experiment 1 (26 Suffolk ewes),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…The semen extenders were; AndroMed [6,7] and two Tris-based extenders containing 297.58 mM Tris, 96.32 mM citric acid, 82.66 mM fructose, 5% (v/ v) glycerol and either 15% (v/v) egg yolk [6,9] or 10% (w/v) BSA [6,8,10]. The three semen extenders have been defined here as AM, BSA and EY for the AndroMed, Tris-based BSA-containing and Tris-based egg yolk-containing solutions, respectively.…”
Section: Semen Preservationmentioning
confidence: 99%
See 2 more Smart Citations
“…The semen extenders were; AndroMed [6,7] and two Tris-based extenders containing 297.58 mM Tris, 96.32 mM citric acid, 82.66 mM fructose, 5% (v/ v) glycerol and either 15% (v/v) egg yolk [6,9] or 10% (w/v) BSA [6,8,10]. The three semen extenders have been defined here as AM, BSA and EY for the AndroMed, Tris-based BSA-containing and Tris-based egg yolk-containing solutions, respectively.…”
Section: Semen Preservationmentioning
confidence: 99%
“…Fukui et al [6] compared the fertility of ewes inseminated intrauterinally with frozen semen using AndroMed (AM) and Tris-based extenders containing BSA or egg yolk and found similar lambing rates among the three semen extenders (56.7, 55.2 and 64.5% for AM and semen extenders containing BSA or egg yolk, respectively). Hiwasa et al [7] also showed that acceptable fertilization rates of superovulated ewes after AI with fresh-diluted or frozen-thawed semen using AM could be obtained in the field. To the best of our best knowledge, there is no report on survival and sperm character-istics of frozen-thawed semen diluted with a synthetic semen extender (AM) at different storage temperatures in baleen whales, including Bryde's whales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is necessary to adjust the technique to achieve higher pregnancy rates. Laparoscopy has been successfully used for insemination in deer (Asher et al., ; Dradjat, ), goats (Kulaksiz & Daskin, ; Vallet, Baril, Leboeuf, & Perin, ) and sheep (Gourley & Riese, ; Hiwasa, Kohno, Togari, Okabe, & Fukui, ), generating pregnancy rates over 70% with fresh semen and 50% using frozen semen. The technique has also been used to inseminate superovulated ewes with conventional (Armstrong & Evans, ) and SS (de Graaf et al., ) generating over 75% fertilization rates.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy has been successfully used for insemination in deer (Asher et al, 1990;Dradjat, 2004), goats (Kulaksiz & Daskin, 2012;Vallet, Baril, Leboeuf, & Perin, 1992) and sheep (Gourley & Riese, 1990;Hiwasa, Kohno, Togari, Okabe, & Fukui, 2009), generating pregnancy rates over 70% with fresh semen and 50% using frozen semen.…”
Section: Discussionmentioning
confidence: 99%